IMPROVING THE MANAGEMENT OF EDUCATIONAL FACILITIES AND INFRASTRUCTURE TO IMPROVE THE QUALITY OF LEARNING AT PRIVATE SMP KARYA BUNDA MEDAN - Yuli Anggriani Desky; Nabilah Nasution; Emeliya Sukma Dara Damanik (XXXXXXXX, 2024)
The purpose of this research is to describe the management of facilities and infrastructure at the Karya Bunda Private Middle School in Medan. This research method uses descriptive qualitative research. The subjects in this study were principals and teachers. The conclusion of this study shows that the planning and procurement of facilities and infrastructure carried out by the principal is in accordance with the provisions, the inventory of school facilities and infrastructure has been carried out properly, the distribution is carried out directly and indirectly, the maintenance of school facilities and infrastructure is carried out periodically and incidentally, supervision and accountability (reporting) of school facilities and infrastructure is carried out by the principal and is carried out once a year during the new school year.